Addressing 21st Century Challenges in Education: An Ecocritical Conceptual Framework toward an Ecotistical Leadership in Education - Lupinacci, John Joseph (Impacting Education: Journal on Transforming Professional Practice, 2017)
This article critiques the notion of individually-focused notions of leadership, instead offering an ecocritical conceptual framework that works to support education at all levels with the aim of recognizing the importance of how leaders in Western industrial culture think, act, and thus organize communities. This framework is applied to examine the potential for EdD programs to critically (re)imagine the role K-12 and higher education institutions might play in reinterpreting how leadership might be (re)constituted—as local and in support of social justice and sustainability. From this lens, the article explores how 21st century challenges that emerge from the complex intersections of social justice and sustainability might be addressed through EdD program development, supportive program structures, and course content influencing teacher education and K-12 school leadership. Calling for a particular kind of leadership supportive of social justice and sustainability, this article shares examples from the authors own practice, program structures, curriculum, and future research.